Childhood Maltreatment: Experiences and Perceptions Among Chinese Young People - Ni, Yanyan (Journal of interpersonal violence, 2021)
The study aimed to investigate young Chinese people’s childhood and adolescence exposure to maltreatment from all types of perpetrators, and to explore their perceptions of such experiences. A cross-sectional study was carried out among 1,255 young people at three universities located in Zhejiang Province, Eastern China. A questionnaire drawing on validated tools was developed to measure childhood and adolescence exposure to physical and emotional maltreatment. Physical and emotional maltreatment by any perpetrator before the age of 18 years was reported by 83.3% and 85.9% of the students, respectively; extreme forms were not rare. Overall, 68.8% of the students reported physical maltreatment by parents, 56.1% by teachers, 29.8% by peers, 11.7% by siblings, and 9.1% by grandparents; 58.5% reported emotional maltreatment by parents, 43.3% by teachers, 53.3% by peers, 12.0% by siblings, and 10.0% by grandparents. Physical or emotional maltreatment by any perpetrator was common in all sociodemographic groups, irrespective of urban/rural residence and economic status. Risk factors for maltreatment differ with type of maltreatment and perpetrator. Personal experience of emotional maltreatment was generally perceived as more harmful and less acceptable than physical, especially in females. In conclusion, high levels of maltreatment of children and adolescents in China indicate the need for (a) parent education about appropriate discipline measures when raising children, (b) teacher education and enforcement of existing laws banning institutional corporal punishment, (c) the adoption of a comprehensive anti-bullying strategy, and (d) the development of a formal child protection system to protect and support the most vulnerable families.